Development and validation of the Transgender Adolescent Stress Survey–Minority Stress (TASS-MS) - Goldbach, Jeremy T.; Schrager, Sheree M.; Wood, Jules K.; O’Brien, Rory P.; Dunlap, Shannon L.; Rhoades, Harmony (Frontiers in Psychology, 2024)
Objective: This study aimed to create and validate a novel measure of gender-related minority stress in transgender and nonbinary adolescents (TNBA). TNBA face higher risks of varied behavioral health concerns compared to their cisgender peers, a disparity often attributed to the presence of minority stress due to discrimination. To date, no comprehensive measures of gender-related minority stress exist for use with TNBA.Method: The present study recruited a U.S. national sample (N = 444, aged 12-17; 65.5% White, 9.5% Black, 9.5% Latine, 15.5% other ethnicity; 34.7% transmasculine, 17.3% transfeminine, 38.3% nonbinary, 9.5% agender) of TNBA. An initial item pool was developed from life history calendars, a modified Delphi process, and cognitive interviews with TNBA. Analytic methods including principal components analysis, item response theory, measurement invariance testing, and reliability analyses were conducted to establish the final scale. Concurrent validity was established across behavioral outcomes (mental health, suicidal thoughts and behavior, substance use), and convergent and divergent validity compared the Transgender Adolescent Stress Survey-Minority Stress (TASS-MS) to existing measures of gender-related minority stress.Results: The TASS-MS and its subscales (disaffirmation, visibility and internalized transnegativity, family) were significantly associated with anxiety and depressive symptoms, PTSD symptoms, suicidal behaviors, nonsuicidal self-injury, marijuana, and prescription drug use. The TASS-MS was moderately and weakly correlated with convergent and divergent measures, respectively, indicating specificity to minority stress. Conclusions: The TASS-MS is a reliable and valid measure for future research with TNBA. It is inclusive and usable by all gender minority adolescents, uses a standard simple scoring system, and assesses adolescent-specific stressors.